Pathway to understand liquid metal embrittlement (LME) in Fe-Zn couple: From fundamentals toward application. (August 2021) - Razmpoosh, M.H.; DiGiovanni, C.; Zhou, Y.N.; Biro, E.
Abstract: Liquid metal embrittlement (LME) has been reported in many structural materials including steel, aluminum, brass, and nickel during hot-working processes e.g. welding, hot-deformation, brazing, heat-treatment, or in-service time. In many of the applications, such as automotive, aerospace, nuclear industries, LME is considered as a serious safety concern. Over the last decades, research activities have grown considerably striving to understand the abnormal LME phenomenon. However, a fundamental understanding of LME has not yet been unraveled due to the diverse, contradicting proposed mechanisms in different processing routes and materials. In the present overview, first various proposed mechanisms are integrated into a systematic manner. Revisiting the proposed mechanisms based on the most-recent experimental discoveries reveals that the stress-assisted grain boundary diffusion mechanism is a viable LME mechanism. The connection between sub-atomic (electronic) structure modification and the embrittlement at grain boundaries provides insights into the grain boundary decohesion during LME. In a bottom-up approach, then this overview selects Zn-induced embrittlement during assembly welding as an example case of LME. Explanations are provided to show why LME cracks are both seen to degrade and be innocuous to material's performance. Finally, this review outlines recommended directions for future research steps to overcome LME-cracking risk, both from material and process aspects.